SEKULARISME DAN ISU-ISU GERAKAN UMAT ISLAM - Indriyani, Dian; Andriyani, Andriyani (Nurani, 2017)
In its history, politically, liberalism of Islam accepts deep momentum during Sultanate-Autonomy in Turkey, where Islamic countries, especially Turkey and Egypt, which had got in touch with western world, had big influences toward Islamic societies’ attitude. This influence made the Turkish and the Egyptian understands rigid. Islamic scholars of law seem confused to see new thing in Islamic societies. A case will directly be instructed “illegal” or haram if the case itself cannot be found in the school of Hanafi’s classical books. Then, this paper is intended to contribute some points of view of this school by means of answering some main questions about the truth of Islamic liberal considered as a secular movement under the guise of Moslem, the truth of the discourse of Islamic liberalism presents the past for the sake of modernization and the truth of Islamic liberalism that is irrelevant to the Indonesian culture.